Structural racism and racialization of Roma/Ciganos in Portugal: The case of secondary school students during the COVID-19 pandemic - Magano, O. (2021)
The aim of this article is to contribute to the analysis of the structural racism and racialization that exists in Portugal against Roma people. Racialization takes place in various dimensions of life, but we will focus here on issues of schooling and education, which were accentuated during the COVID-19 pandemic and revealed a lack of social deprotection and inequalities between Roma and non-Roma students. This analysis, focusing on the impact on young people attending secondary education, is based on a qualitative study carried out in the Metropolitan Areas of Lisbon and Porto using data from three focus groups and in-depth interviews with 33 secondary school students. Several public policies currently cover the Roma/Ciganos, but social inequality persists in terms of basic subsistence conditions and civic participation, as well as in the form of structural racism, with little Roma participation in political life and the invisibility of representation. The situation has worsened exponentially due to the COVID-19 pandemic, with the combination of “classic” forms of racism and discrimination and the new forms of exclusion that have also appeared. We argue that the implicit acceptance of poverty and marginalization among Roma people needs to be viewed as a component of the racialization and antigypsyism to which they are subjected, and this dimension needs to be further investigated by scientific agendas.